2009
DOI: 10.1111/j.1756-1051.2009.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers of some species of Salvia (Lamiaceae) from the Sichuan Province, China

Abstract: The present study reports the chromosome number of 12 accessions belonging to 10 species of Salvia from the Sichuan Province in China. Most accessions have the chromosome number 2n=2x=16. However, three species (S. evansiana, S. przewalskii and S. brevilabra) are tetraploid with a chromosome number of 2n=4x=32. A B‐chromosome was observed in S. tricuspis. The basic chromosome number x=8 was inferred for all accessions studied. The chromosome number of all the species was determined for the first time, except f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
(16 reference statements)
1
14
2
Order By: Relevance
“…Kress and Erickson (2007) pointed out that ITS has multiple copies in the nuclear genome and it varies within species, which limits its application. In contrast to Salvia, most of these copies were diploids Yang et al, 2009). The intraspecific variations were only higher than that of rbcL.…”
Section: Applicability Of Nritsmentioning
confidence: 91%
“…Kress and Erickson (2007) pointed out that ITS has multiple copies in the nuclear genome and it varies within species, which limits its application. In contrast to Salvia, most of these copies were diploids Yang et al, 2009). The intraspecific variations were only higher than that of rbcL.…”
Section: Applicability Of Nritsmentioning
confidence: 91%
“…However, Nakipoğlu (1993a, b) found that Salvia taxa have B type chromosomes. Also, Alberto et al (2003) and Yang et al (2009) found that Salvia taxa have B type chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…taxa have 2n=12-64 chromosome numbers (Afzal-Rafii 1976, 1980, Haque and Ghoshal 1980, Haque 1981, Nakipoğlu 1993a, b, Ozdemir and Senel 1999, Tunamoto et al 2000, Alberto et al 2003, Zhiyun et al 2004, Ozkan 2006, Ozkan and Soy 2007, Yang et al 2009, Masoudi et al 2010, Zhen-Qiao et al 2010, Sheidai and Alijanpoo 2011, Martin et al 2011. Although cytological studies are abundant, karyological studies about Salvia taxa growing in Turkey are little (Martin et al 2011(Martin et al , 2015.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that polyploidy is at least one of the evolutionary strategies of Salvia species in this area . In several cases, as for the Chinese Salvia species in the Webbia Hengduanshan Mountains region examined by Yang et al (2004Yang et al ( , 2009, polyploidization is a minor factor in sympatric speciation; instead, variation of karyotype structure at the diploid level seems to be the predominant feature of the chromosomal evolution of the species (Yang et al 2004). Alberto et al (2003) suggested that plant habit would not seem to relate to the level of ploidy.…”
Section: Variations Of the Chromosome Number And Ploidy Level In Genumentioning
confidence: 96%
“…In the Hengduanshan Mountains of China -a probable centre of speciation and diversification of Salvia (Wu and Li 1982) -x = 8 is the dominant chromosome base number (92.8%) and x = 7 and x = 9 occur less frequently (each 3.6%). Yang et al (2009) described speciation in this region besides the occurrence of polyploidy, occurring by variation of chromosome structure and isolation speciation from a stock of 2n = 16 ). In India, as in China, x = 8 is predominant (49.3%) and x = 10, 11 and 13 have each been reported once.…”
Section: Biogeographymentioning
confidence: 98%